Al-Anāṣir al-Dākhiliyah fī Masraḥiyah al-Aydī al-Nāʽimah li Taufīq al-Ḥakīm: Dirāsah Adabiyah - Alu , Sri Utami Devy (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2021)
One of the modern Arabic literary figures who wrote many drama scripts is Taufiq al-Hakim. The beauty, and uniqueness of the drama script he produced made researchers interested in researching one of his dramas entitled Soft Hands or Al-Aydi an-Na'imah. This research was written to analyze the intrinsic elements in the drama script Al-Aydi an-Na'imah by Taufiq Al-hakim. The object of this research is the drama script Al-Aydi an-Na'imah then this object is examined by qualitative descriptive research methods, qualitative research is observative and usually, the data presented is in the form of words.